A new model for inclusive seed delivery: Lessons from a pilot study in Kenya: Leveraging champion farmers’ entrepreneurial know-how to reach the last mile - Kramer, Berber; Waweru, Carol; Waithaka, Lilian; Eyase, Jean; Chegeh, Joseph; Kivuva, Benjamin; Cecchi, Francesco (International Food Policy Research Institute, 2021)
Climate change has exacerbated the frequency and severity of extreme weather events affecting the livelihoods of millions of smallholder farmers across Sub-Saharan Africa. Risks such as increased droughts, pests, floods, and heatwaves are projected to increase significantly in future years. The formal seed sector is an important entry point to help farmers better manage these risks, as it provides access to high-quality certified seeds of improved stress-tolerant varieties, selected and bred to maximize productivity in good years, whilst reducing the impact of climate change risks in bad years. The challenge, however, is that the formal market is not always inclusive and is more accessible to middle- or largescale (and often male) farmers. Smaller farmers (often female) are more likely to obtain seeds from informal sources (friends or peers) or collect their own seeds from the crops they grow. This creates social inequities in distribution channels for quality seeds; and in qualitative research, farmers informed us that the COVID-19 pandemic has further restricted their access to inputs.